Sate Padang Sumatera Barat Sebagai Gastronomi Unggulan Di Indonesia - Rahmad Sani, Maulana; Nur Alia, Mirna; Riyadi, Dony (Universitas Pendidikan Indonesia, 2016)
Sate Padang is a typical food of West Sumatra and one part traditionalIndonesian food heritage. There are various types of Sate Padang circulating indifferent areas of West Sumatra, which each have a historical background, spiceblend, and different processing. This study aimed to obtain satay as one gastronomic ethnic / ethical Padang.This research was conducted using qualitative methods with data collectionthrough in-depth interviews, participant observation, literature, and documentation study.The results showed there were some kind of Sate Sate Padang includeDangung-Dangung, Peanut Sate Dangung-Dangung, Sate Padang Panjang, SateBatusangkar, and Sate Pariaman. Each type of satay had a history, type of seasoning, processing, and marketing techniques of its own. Until now, Sate Padang as one of the specialties of West Sumatra are much in demand by domestic and foreign tourists, but not have a patent as rendang Padang. Strategic efforts are needed, especially from the government and employers Sate Padang to preserve and popularize it with patents.